Measurement of the W boson helicity in top quark decays using 5.4 fb(-1) of p(p)over-bar collision data - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Ancu, L. S.; Van Leeuwen, W. M.; et al. (Amer Physical Soc, 2011)
We present a measurement of the helicity of the W boson produced in top quark decays using t (t) over bar decays in the l + jets and dilepton final states selected from a sample of 5.4 fb(-1) of collisions recorded using the D0 detector at the Fermilab Tevatron p (p) over bar collider. We measure the fractions of longitudinal and right-handed W bosons to be f(0) = 0.669 +/- 0.102[+/- 0.078(stat.) +/- 0.065(syst.) +/- and f(+) = 0.023 +/- 0.053[+/- 0.041(stat.) +/- 0.034(syst.)], respectively. This result is consistent at the 98% level with the standard model. A measurement with f(0) fixed to the value from the standard model yields f(+) = 0.010 +/- 0.037[+/- 0.022(stat.) +/- 0.030(syst.).].